(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2015)
This article describes synthesis and characterization of novel ligand, 3-(2-pyridyl)-5-cyclopropyl-1,2,4-triazole (HL) and palladim(II) complex, Pd(HL)Cl2. The crystal and molecular structure of the complex was determined by X-ray diffraction analysis. Both compounds were characterized by means of UV-VIS, IR- and 1H NMR-spectroscopy. The synthesis of ligand (HL) based on thermal cyclization of amidrazons obtained by acylation of hydrazides with imidoesters. One of the features of 1,2,4-triazoles is that they can exist in three tautomeric forms. As a result we observe doubling and tripling of signals of protons in NMR-spectra of the corresponding compounds. On the basis of obtained ligand we synthesized coordination compound in the metal to ligand molar ratio 1 to 1 Pd(HL)Cl2: PdCl2×2CH3CN + HL => Pd(HL)Cl2. Adduced to NMR-spectra of obtained complex, compared with non coordinated ligand there is no doubling of signal of the N-H triazole proton, which is explained by stabilization of some conformation by chelation. It is necessary to highlight that after complexation protons of pyridine and triazole fragments undergo low-field shift because of decrease in electron density in the corresponding heterocyclic. The results of NMR-spectra were confirmed by the results of X-ray analysis. It became known, that complexation process leads to increse of optical density and appearance of second maximum in a long-wave area in absorption-spectra.